Transformative Impact of Blockchain and Iot Integration in Healthcare - Shaik, Nadiah Jaffreen; Santhisri, Tatavarthy (Journal of Neonatal Surgery, 2025)
Blockchain and IoT are transforming healthcare by enhancing data interchange, patient data security, and operational efficiency. Blockchain's decentralized ledger system protects medical data, lowers errors, and improves integrity. It increases healthcare data access transparency, accountability, and flexibility. Internet of Medical Things (IoMT) devices use blockchain authentication for secure health monitoring and healthcare operations. Cloud and fog computing are improving staff satisfaction and patient safety by storing and analyzing IoT data. Global e-health policies and regulations are essential for healthcare IoT and cloud computing development. Addressing privacy and security problems requires industry-specific security frameworks. Healthcare's IoT problems and potential are determining its future. This abstract explores the security and operational concerns of blockchain and IoT integration in healthcare and its transformational potential..